Penguatan Ekonomi di Sektor Hilir: Strategi Pengelolaan Keuangan untuk Keberlanjutan UMKM di Era Digital - Izza Ashsifa; Muhammad Teguh Kuncoro (Jurusan Akuntansi Fakultas Ekonomu Universitas Sriwijaya, 2023)
This community service aims to enhance financial management in Micro, Small, and Medium Enterprises (MSMEs) in the downstream sector of the coffee industry, with CAK COFFEE as the primary collaborator. The implementation focuses on CAK COFFEE, a Micro, Small, and Medium Enterprise (MSME) that has established itself as a prominent and inventive participant in the domestic coffee sector. The identified difficulties are due to the financial limitations experienced by CAK COFFEE, which include inefficient cash management and exposure to economic uncertainties. The execution involves providing financial literacy training, implementing financial information systems, and conducting risk management workshops. The community service method focuses on an inclusive approach involving owners, employees, and important stakeholders in decision-making. CAK COFFEE has shown greater efficiency and enhanced financial management skills as a result of this program. This community service activity benefits CAK COFFEE by promoting improved financial management skills through financial literacy and optimal exploitation of financial information systems. The success of this undertaking acts as a source of motivation for other Micro, Small, and Medium Enterprises (MSMEs), encouraging improved effectiveness in operations and business expansion. The existing partnerships enhance the MSME ecosystem in the downstream industry.